Property patterns for the formal verification of automated production systems - Campos, J. Creissac (2008)
In recent years, several approaches to the analysis of automation systems dependability through the application of formal verification techniques have been proposed. Much of the research has been concerned with the modelling languages used, and how best to express the automation systems, so that automated verification might be possible. Less attention, however, has been devoted to the process of writing properties that accurately capture the requirements that need verification. This is however a crucial aspect of the verification process. Writing appropriate properties, in a logic suitable for verification, is a skilful process, and indeed there have been reports of properties being wrongly expressed. In this paper we put forward a tool and a collection of property patterns that aim at providing help in this area.